CA1 Neurons Acquire Rett Syndrome Phenotype After Brief Activation of Glutamatergic Receptors: Specific Role of mGluR1/5 - Balakrishnan, Saju; Mironov, Sergej L. (Frontiers in Cellular Neuroscience, 2018)
Rett syndrome (RTT) is a neurological disorder caused by the mutation of the X-linked MECP2 gene. Neurophysiological hallmark of RTT phenotype is the hyperexcitability of neurons that represent a cause of frequent epileptic attacks in the patients. This feature may stem from impaired glutamate handling in RTT but the concerning experimental data are yet lacking. We previously reported that the RTT hippocampal slices frequently show aberrant glutamate transients associated with repetitive burst firing in the CA1 neurons. We here examined the roles of ionotropic, and specifically, metabotropic glutamate receptors (GluR) in regulation of ambient glutamate handling and excitability in hippocampal organotypic slice from wild-type (WT) and Mecp2-/y mice (RTT). Stimulation of AMPA, kainate, NMDA and mGluR1/5 receptors in both WT and RTT slices induced a global release of glutamate measured with fluorescence sensor (iGluSnFr) expressed in CA1 neurons. The neuronal activity was transiently augmented and then depressed, respectively. After wash out of the agonists from WT slices, repetitive glutamate transients were established, whose pattern resembled that of naive RTT slices. In both neuronal types, the GluR agonists also induced delayed and long-lasting decrease in hyperpolarization-activated (HCN) and increase in voltage-sensitive calcium channel (VSCC) currents. The repetitive glutamate transients we reinforced by agonists to mGluR1/5 and their antagonists suppressed glutamate spikes. Postsynaptic modifications of activity were examined using a non-stationary noise analysis and back-propagating potentials (bAPs). After single application of glutamate agonists the single channel current and the number of postsynaptic calcium-permeable AMPARs increased. bAPs, which normally evoked afterdischarges lasted both in WT and RTT for ~2 min, were augmented by mGluR1/5 agonist. The effects were occluded by intracellular perfusion with AMPAR blocker and unchanged by NMDAR antagonist. We propose that glutamate release in RTT hippocampus stimulates extrasynaptic mGluR1/5 that modifies somatic and postsynaptic channels and make neurons hyperexcitable and more prone to spontaneous glutamate release.